Large Scale Genomic Instability as an Additive Prognostic Marker in Early Prostate Cancer - Maria E. Pretorius; Håkon Wæhre; Vera M. Abeler; Ben Davidson; Ljiljana Vlatkovic; Ragnhild A. Lothe; Karl-Erik Giercksky; Håvard E. Danielsen (Cellular Oncology)
Background: The clinical outcome for the individual prostate cancer patient is often difficult to predict, due to lack of reliable independent prognostic biomarkers. We tested DNA ploidy as a prognostic factor for clinical outcome in 186 patients treated with radical prostatectomy.